The Bad Guys in the furball strikes back - Blabey, Aaron (New York, NY : Scholastic Inc., 2016)
"Mr. Wolf and his bad buddies have messed with the wrong guinea pig--one who is secretly an evil mad scientist. And the nasty little furball wants revenge!"--Back cover.
2.5
3-6
3-6
Keywords: Animals -- Comic books, strips, etc. -- Juvenile fiction; Chickens -- Comic books, strips, etc. -- Juvenile fiction; Heroes -- Comic books, strips, etc. -- Juvenile fiction; Rescues -- Comic books, strips, etc. -- Juvenile fiction; Animals -- Fiction; Chickens -- Fiction; Heroes -- Fiction; Rescues -- Fiction; Animals -- Comic books, strips, etc. -- Fiction; Chickens -- Comic books, strips, etc. -- Fiction; Heroes and heroines -- Comic books, strips, etc. -- Fiction; Rescue work -- Comic books, strips, etc. -- Fiction; Graphic novels; Humorous comics